New Insights Into Marburg Virus Disease Pathogenesis in the Rhesus Macaque Model. (19th July 2018) - Cooper, Timothy K; Sword, Jennifer; Johnson, Joshua C; Bonilla, Amanda; Hart, Randy; Liu, David X; Bernbaum, John G; Cooper, Kurt; Jahrling, Peter B; Hensley, Lisa E
Abstract: Previously, several studies have been performed to delineate the development and progression of Marburg virus infection in nonhuman primates (NHPs), primarily to clarify the mechanisms of severe (fatal) disease. After the 2013–2016 Ebola virus disease (EVD) epidemic in Western Africa, there has been a reassessment of the available filovirus animal models and the utility of these to faithfully recapitulate human disease. The high lethality of the NHP models has raised doubts as to their ability to provide meaningful data for the full spectrum of disease observed in humans. Of particular interest are the etiologic and pathophysiologic mechanisms underlying postconvalescent sequelae observed in human survivors of EVD and Marburg virus disease (MVD). In the current study, we evaluated the lesions of MVD in NHPs; however, in contrast to previous studies, we focused on the potential for development of sequelae similar to those reported in human survivors of MVD and EVD. We found that during acute MVD in the macaque model, there is frequent inflammation of peripheral nerves, autonomic ganglia, and the iris of the eye. Furthermore, we demonstrate viral infection of the ocular ciliary body and retina, testis, epididymis, ovary, oviduct, uterine endometrium, prostate, and mammary gland. These findings are relevant for both development of postconvalescent sequelae and the natural transmission of virus.